2017
DOI: 10.1007/s00586-017-5375-1
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar total disc replacement: predictors for long-term outcome

Abstract: Patients with Modic changes prior to the TDR surgery were more likely to report a clinically important functional improvement at long-term follow-up. Comorbidity, low level of education, long-term sick leave and high ODI score at baseline were associated with unemployment at long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 37 publications
1
12
0
1
Order By: Relevance
“…The study is an 8-year follow-up of a randomized multicentre study conducted at five university hospitals across Norway [32]. The trial included 173 patients aged 25-55 years randomised to rehabilitation or lumbar total disc replacement.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study is an 8-year follow-up of a randomized multicentre study conducted at five university hospitals across Norway [32]. The trial included 173 patients aged 25-55 years randomised to rehabilitation or lumbar total disc replacement.…”
Section: Data Collectionmentioning
confidence: 99%
“…The study reported here is the first to consider the concurrent measurement properties of the two versions of the EQ-5D, administered at long-term follow-up, to patients with severe LBP randomized to rehabilitation or surgery with disc prostheses [14,32]. The two versions are evaluated according to recognized measurement criteria for PROMs including those that have been used in previous comparisons of the 3L and 5L [9,[17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The commonly used Pfirrmann system [33] provides a single rating of disc degeneration based on the height, structure and signal of the disc, and the distinction of nucleus and annulus. This system does not separate disc signal from disc height, and it does not include disc contour/herniation or HIZnor Modic changes, which were related to clinical outcome after TDR in our cohort in both the short- [34] and long-term [35].…”
Section: Discussionmentioning
confidence: 99%
“…The commonly used Pfirrmann system [32] provides a single rating of disc degeneration based on the height, structure and signal of the disc, and the distinction of nucleus and annulus. This system does not separate disc signal from disc height, and it does not include disc contour/herniation or HIZnor Modic changes, which were related to clinical outcome after TDR in our cohort in both the short- [256] and long-term [283]. Increased ADD (yes/no) was a mainly qualitative variable.…”
Section: Adjacent Disc Degeneration (Add)mentioning
confidence: 93%